Genome-wide prediction of DNase I hypersensitivity using gene expression - Weiqiang Zhou (Nature Portfolio, 2017)
A map of the activities of all genomic regulatory elements across cell types and conditions would be a tremendous resource. The computational method introduced here predicts genome-wide accessible sites from gene expression data and allows the authors to build a database of regulatory element activities using publicly available transcriptome data.